Stability of Hierarchical Triples Comprising a Central Massive Body and a Tight Binary: The Effect of Inner and Outer Eccentricities on the Binary Breakup Condition - Toshinori Hayashi; Alessandro A. Trani; Yasushi Suto (The Astrophysical Journal)
We explore the stability of gravitational triple systems comprising a central massive body and a tight binary of less massive pairs. In the present paper, we focus on improving the Hill-type stability criterion for the binary in those systems, with particular attention on the effects of the eccentricities of the inner and outer orbits. We perform direct Newtonian N -body simulations over much longer integration times than previous studies, which is essential to determine the stability and breakup timescale distributions of those systems in a reliable fashion. As a result, we obtain an empirical fitting formula of the binary breakup condition that incorporates effects of the inner and outer eccentricities, the mutual inclination of the inner and outer orbits, the mass ratios of the three bodies, and the breakup timescale.